Identity Crisis in the Novel Cuffs of Papers for Yusef Hadi Mays - Ghada Jamal Makki (College of Education for Women, 2018)
This research deals with the study of the identity lost in the novel (handcuffs of paper) by Writer (Kuwaiti / Iraqi ) Yousif Hadi Mays.This is because of The strange subject presented by the writer ,Kuwait has chosen a sbace for his novel and chose apurely Kuwaiti theme. Hence the importance of the novel, as it came to the subject of identity completely dntdiffere from what we wwrote after the fall off the regime (2003), Which is related to the last coming from outside the country, which remained oscillataing between his mother,s identity where language, religion and history and  the identity of the other by virtue and dazzling, and integration and here con not belong to either party. This is a violation of the taboos of prevention and the presentation of a topic is the talk of the hour as presented the nature of policies based on interests and reconsider the issue of human rights in the light of the changes taking place and rapid developments in the world. The first section deals with the conflict of identities , the second is the struggle of ideologies, then the conclusion and the list of sources.